Roma Index and Adnex Model: which is more Superior in Predicting Epithelial Ovarian Malignancy? Index Roma dan Model Adnex: Manakah yang Lebih Unggul dalam Memprediksi Keganasan Ovarium Epitelial? - Feibyg Lumandung; Suzanna P. Mongan; Bismarck J. Laihad (Indonesian Socety of Obstetrics and Gynecology, 2023)
Objective: To compare the accuracy of ROMA index andADNEX model in predicting the risk of malignancy in ovariantumour.Methods: This was a prospective analytic study. A total of 37samples were acquired from women of all ages diagnosedwith an ovarian cystic tumour in the Central General HospitalProf. Dr. R. D. Kandou. A CA-125 marker, HE4 marker,menopausal status and ultrasonography (USG) examinationwere obtained, and subsequently compared with the fi nalhistopathological results. The data were analysed by usingthe SPSS statistics software.Results: Thirty-seven women participated in this study. Themean age of participants was 43 years old. The Area UnderCurve (AUC) of the ADNEX was 0.979 with a sensitivity of90.0%, specifi city of 88.2%, negative predictive value of89.8%, and positive predictive value of 80.5%. The AUC ofthe ROMA model was 0.734 with the sensitivity, specifi city,negative predictive value, and positive predictive value of65.0%, 64.7%, 64.8%, and 64.8%, respectively. Both modelsshowed AUC values > 0.50 (p-value < 0.05).Conclusions: The IOTA ADNEX had better accuracy than theROMA model in predicting ovarian epithelial malignancy.The ADNEX model had higher sensitivity and specifi city thanthe ROMA model.Keywords: ADNEX, CA-125, HE4, Ovarian tumour, ROMAAbstrakTujuan: Untuk membandingkan akurasi indeks ROMAdan ADNEX model dalam memprediksi keganasan tumorovariumMetode: Penelitian ini merupakan studi analitik prospektif.Total 37 sampel penelitian didapatkan dari wanita yangdidiagnosa tumor ovarium kistik di RSUP Prof. Dr. R. D.Kandou. CA-125, HE4, status menopause dan pemeriksaanUSG dilakukan, dan dibandingkan dengan hasil histopatologi.Data kemudian dianalisa menggunakan program statistikSPSS.Hasil: Tiga puluh tujuh perempuan yang berpartisipasidalam penelitian ini. Dengan rerata usia 43 tahun. TotalArea Under Curve (AUC) dari IOTA ADNEX adalah 0,979dengan sensitivitas 90,0%, spesifi sitas 88,2%, nilai prediksinegatif 89,8%, dan nilai prediksi positif 80,5%. AUC darimodel ROMA adalah 0,734 dengan sensitivitas, spesifi sitas,nilai prediktif negatif dan nilai predikitif positif 65.0%, 64.7%,64.8%, dan 64.8% berturut-turut. Kedua model menunjukkannilai AUC > 0,50 (nilai p <0,05).Kesimpulan: IOTA ADNEX memiliki akurasi yang lebih baikdibandingkan model ROMA dalam memprediksi keganasanovarium epithelial. ADNEX model memiliki sensitivitas danspesifi sitas lebih tinggi dibandingkan model ROMAKata kunci: ADNEX, CA-125, HE4, ROMA, Tumor Ovarium.